2004
DOI: 10.1007/s00436-004-1084-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of parasitism on the pharmacokinetics of moxidectin in lambs

Abstract: Most pharmacokinetic studies on anthelmintic drugs have been performed on non-parasitized animals. However, it seems likely that the parasite burden could influence the deposition of such drugs. The pharmacokinetics of moxidectin administered orally and by subcutaneous injection was compared in lambs exposed to nematode infection and in parasite naive lambs. Plasma samples were analyzed for moxidectin over 40 days post-treatment. The main pharmacokinetic parameters calculated demonstrated a significant change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
4
19
0
Order By: Relevance
“…These results are in agreement with our previous study, which demonstrated that parasitism induced significant changes in DRM disposition and availability, changes that are associated with a greater drug clearance, in comparison with the parasite-naive animals (Pérez et al 2007). Similarly, other studies have shown that the duration for moxidectin action may be reduced when the nutritional stress of parasitic disease affects body condition (Hennessy and Alvinerie 2002;Lespine et al 2004). …”
Section: Analytical Methodology Validationsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in agreement with our previous study, which demonstrated that parasitism induced significant changes in DRM disposition and availability, changes that are associated with a greater drug clearance, in comparison with the parasite-naive animals (Pérez et al 2007). Similarly, other studies have shown that the duration for moxidectin action may be reduced when the nutritional stress of parasitic disease affects body condition (Hennessy and Alvinerie 2002;Lespine et al 2004). …”
Section: Analytical Methodology Validationsupporting
confidence: 92%
“…As previously demonstrated (Pérez et al 2007), gastrointestinal parasitism induces significant changes in plasma disposition and DRM availability in subcutaneously treated lambs. Similar effects in sheep have been described for moxidectin (Lespine et al 2004) and ivermectin (Pérez et al 2006).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…On the day of treatment, counts for calves of the Ivomec Plus group were significantly lower than counts for calves of the other two treatment groups. This uneven dispersal of patent infections prior to day0 may have beneficially biased the perceived effectiveness of Ivomec Plus relative to the other products in the test as fecal egg counts and drug availabilities have been shown to be negatively correlated (Perez et al 2006;Lespine et al 2004). In this test, however, neither ivermectin product significantly reduced egg counts, whereas treatment with Means with no lowercase letter in common differ (P < 0.05) were most heavily dependent upon class of treatment compound as opposed to animal source and are therefore summarized on a class of compound basis across all tests and sample dates in Fig.…”
Section: Fecal Egg Count Reductionsmentioning
confidence: 98%
“…MLs are characterized by a unique long mean residence time (MRT) in the host associated with long-lasting activity when compared with other anthelmintics such as benzimidazoles. The pharmacokinetic behavior of MLs depends upon the route of administration, the formulation used, the animal species, and pathophysiological status of the host (Alvinerie et al 1998;Baggot and McKellar 1994;Bassissi et al 2004b;Hennessy and Alvinerie 2002;Lespine et al 2004;Perez et al 2002). Ivermectin is available for oral, subcutaneous, and topical administration.…”
Section: Introductionmentioning
confidence: 99%